The influence of macrophytes in the population structure of Palaemon pandaliformis (Stimpson, 1871) in Salsa River, Bahia state, northeast Brazil - Paschoal, Lucas Rezende Penido [UNESP]; Guimaraes, Fernanda Jordao; Couto, Erminda Da Conceicao Guerreiro (Instituto de Ecologia y Ciencias Ambientales (IECA), 2024)
The aim of this study is to evaluate the role of three species of macrophytes in the population dynamics of the amphidromous shrimp Palaemon pandaliformis. Results revealed that macrophytes perform important functions and are directly responsible for modulating spatial distribution of this species.
A influência de macrófitas na estrutura populacional de Palaemon pandaliformis (Stimpson, 1871) no Rio Salsa, estado da Bahia, nordeste do Brasil
Keywords: camarões fitófilos; Caridea; distribuição espacial; habitat preferences; phytophilous shrimps; preferência de habitats; spatial distribution